Sengketa Perbankan Syariah : Inovasi Dan Tantangan - Nurfadillah, Nurfadillah; Nabila, Ainun; Risnah, Risnah; Wahid, St. Khadijah (Yayasan Abdurrauf Cendekia Nusantara, 2025)
Disputes in Islamic banking are becoming an increasingly important topic in line with the rapid growth of the Islamic financial sector in various countries, including Indonesia. banking system based on sharia principles, which prohibits usury and prioritizes justice and openness, sharia banking faces several challenges in resolving conflicts. This article reviews innovations and challenges in handling conflicts in Islamic banking, with an emphasis on regulations, resolution mechanisms, and their impact on the continuity of the Islamic financial sector. Innovations in handling conflicts in sharia banking include the establishment of sharia-based arbitration institutions, the application of digital technology such as blockchain to increase contract transparency, as well as hybrid methods that combine litigation and non-litigation processes. In Indonesia, for example, the National Sharia Arbitration Board (BASYARNAS) has an important function as an alternative forum for resolving disputes. In addition, advances in regulations, such as Law no. 21 of 2008 concerning Sharia Banking, provides a clearer legal framework to regulate various operational aspects and dispute resolution. However, the biggest challenges faced are the parties' low understanding of sharia principles, the lack of skilled human resources in the fields of sharia law and finance, and the possibility of jurisdictional conflicts between religious courts and general courts. In addition, differences in the interpretation of sharia contracts are often the root of the problem, requiring a specific approach to be in line with maqashid sharia (the goals of sharia). This article also emphasizes the importance of technology in increasing justice and efficiency in conflict resolution. For example, implementing blockchain-based smart contracts can reduce conflict by guaranteeing that agreements are automatically executed according to agreed terms. On the other hand, digitalization also brings new challenges, such as data security and trust in the technology applied. Through an examination of these innovations and challenges, this article reveals the importance of collaboration between government, Islamic financial institutions, and society to build an ecosystem that supports fair and efficient conflict resolution. For the future, strengthening regulations, increasing human resource capacity, and applying the latest technology will be the main factors in overcoming problems and encouraging the sustainability of sharia banking amidst global change. [Sengketa dalam perbankan syariah menjadi topik yang semakin penting seiring dengan pertumbuhan cepat sektor keuangan syariah di berbagai negara, termasuk Indonesia. Sebagai sistem perbankan yang berlandaskan prinsip syariah, yang melarang riba dan mengutamakan keadilan serta keterbukaan, perbankan syariah menghadapi beberapa tantangan dalam penyelesaian konflik. Artikel ini mengulas inovasi serta tantangan dalam menangani konflik di perbankan syariah, dengan penekanan pada regulasi, mekanisme penyelesaian, dan dampaknya terhadap kelangsungan sektor keuangan syariah. Inovasi dalam menangani konflik di perbankan syariah termasuk pembentukan lembaga arbitrase berbasis syariah, penerapan teknologi digital seperti blockchain untuk meningkatkan transparansi kontrak, serta metode hibrida yang menggabungkan proses litigasi dan non-litigasi. Di Indonesia, sebagai contoh, Badan Arbitrase Syariah Nasional (BASYARNAS) telah berfungsi penting sebagai forum alternatif dalam penyelesaian sengketa. Selain itu, kemajuan dalam regulasi, seperti Undang-Undang No. 21 Tahun 2008 mengenai Perbankan Syariah, memberikan kerangka hukum yang lebih jelas untuk mengatur berbagai aspek operasional dan penyelesaian sengketa. Namun, tantangan terbesar yang dihadapi adalah rendahnya pemahaman para pihak mengenai prinsip-prinsip syariah, kekurangan sumber daya manusia yang terampil dalam bidang hukum dan keuangan syariah, serta kemungkinan munculnya konflik jurisdiksi antara pengadilan agama dan pengadilan umum. Selain itu, perbedaan dalam penafsiran kontrak-kontrak syariah sering kali menjadi akar masalah, yang memerlukan pendekatan spesifik agar sejalan dengan maqashid syariah (tujuan syariah). Tulisan ini juga menekankan pentingnya teknologi dalam meningkatkan keadilan dan efisiensi dalam penyelesaian konflik. Contohnya, penerapan kontrak pintar berbasis blockchain dapat mengurangi konflik dengan menjamin bahwa kesepakatan dilaksanakan secara otomatis sesuai dengan ketentuan yang telah disepakati. Di sisi lain, digitalisasi juga membawa tantangan baru, seperti keamanan data dan kepercayaan pada teknologi yang diterapkan. Melalui pemeriksaan terhadap inovasi dan tantangan tersebut, artikel ini mengungkapkan pentingnya kerja sama antara pemerintah, lembaga keuangan syariah, dan masyarakat untuk membangun ekosistem yang mendukung penyelesaian konflik secara adil dan efisien. Untuk masa depan, penguatan regulasi, peningkatan kapasitas sumber daya manusia, dan penerapan teknologi mutakhir menjadi faktor utama dalam mengatasi masalah dan mendorong keberlanjutan perbankan syariah di tengah perubahan global].